Semboyan “Torang Samua Basudara” dalam Interaksi Penganut Kristen dengan Penganut Agama Lain di Manado - Kesia Martini Pesik (KENOSIS: Jurnal Kajian Teologi, 2022)
The motto of torang samua basudara is the unifying spirit of religions in Manado. The image of Manado cannot be separated from the harmony and peace that is maintained continuously. The reality of peace in this city cannot be separated from the motto of torang samua basudara. This motto continues to be lived in the midst of society and becomes a social reality that shows all forms of primordial differences are not obstacles to living together as brothers. This paper specifically wants to describe how the social construction of the motto of torang samua basudara, seen affects the interaction of Christians in Manado with followers of other religions, seen from the Theology of Religions by Paul F. Knitter. This research collects the data by using qualitative research methods with in-depth interviews and literature study. The results showed this harmony cannot be separated from how the society perceive the motto of torang samua basudara and are united in keeping and maintaining harmony and openness in the midst of diversity. The meaning of the motto of torang samua basudara gives a big influence in the interaction of religions. Christians interact with followers of other religions without any discrimination based on religious, ethnic and cultural backgrounds, but all people are considered brothers who love, accept, and help each other. Thus, the interaction of Christians with followers of other religions reflects a model of acceptance. However, the Christian view of salvation reflects a fulfillment model, implying that salvation also exists in other religions but only when it follows the way of Christ. Thus, Christ becomes the fulfillment of religions.AbstractSemboyan torang samua basudara merupakan spirit pemersatu agama-agama di Manado. Citra Manado tidak lepas dari kerukunan dan kedamaian yang terpelihara secara terus-menerus. Adapun realitas kedamaian yang ada di kota ini tidak lepas dari peran semboyan torang samua basudara. Semboyan ini terus dihidupi di tengah-tengah masyarakat dan menjadi realitas sosial yang menunjukkan bahwa segala bentuk perbedaan primordial bukan hambatan untuk hidup bersama sebagai saudara. Tulisan ini secara spesifik ingin mendeskripsikan bagaimana pengaruh penghayatan semboyan tersebut memengaruhi interaksi penganut Kristen di Manado dengan penganut agama lain, ditinjau dari teori Teologi Agama-Agama Paul F. Knitter. Pengambilan data menggunakan metode penelitian kualitatif dengan teknik wawancara mendalam dan studi pustaka. Hasil penelitian menunjukkan bahwa pemaknaan terhadap semboyan torang samua basudara memberikan pengaruh yang besar dalam interaksi agama-agama. Penganut Kristen berinteraksi dengan penganut agama lain tanpa membeda-bedakan sikap yang dilakukan berdasarkan latar belakang agama, suku dan budaya, melainkan semua orang dianggap sebagai saudara yang saling mengasihi, saling menerima, dan saling menolong.